Genotypic characterization of antibiotic-resistant Salmonella Enteritidis isolates in Dakar, Senegal - Amy Gassama Sow; Abdoul Aziz Wane; Mamadou Hadi Diallo; Cheikh Saad-Bouh Boye; Awa Aïdara-Kane (Journal of Infection in Developing Countries)
Background: It is well established that Salmonella enterica is a major cause of food-borne disease worldwide. In Africa, according to the Who Global Salm-Surv country data bank from 2000 to 2002 Salmonella enterica serovar Enteritidis was the most common serotype involved in human salmonellosis. In Dakar this serotype of Salmonella has been reported as a frequent and an increasing cause of human infection. Methodology: The genetic determinants of the antimicrobial resistance of 25 selected multiresistant strains of Salmonella enterica serovar Enteritidis referred to the National Reference Center for Enterobacteria (NRCE) in Dakar were investigated using molecular techniques. Results: All strains carried blaTEM 1 genes. Five harboured three types of class 1 integrons with gene cassettes dfrA15, dfrA1-aadA1 and dfrA7. Multiresistance was due to a 23 Kb conjugative plasmid. DNA fingerprinting by macrorestriction of genomic DNA revealed a single related group suggesting that strains might be clonal. Conclusions: The spread of resistance genes through plasmid transfer plays an important role in the dissemination of antibiotic resistance in enteric pathogens such as Salmonella Enteritidis; the risk of transmissibility of antibiotic resistance between different bacterial strains highlights the urgent need to develop strategies to limit the spread of antimicrobial resistance among bacterial enteropathogens.